2006
DOI: 10.1161/circulationaha.106.639161
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin Has a Crucial Role in Blood Cell–Mediated Vascular Repair

Abstract: Background-Endoglin, an accessory receptor for transforming growth factor-␤ in vascular endothelial cells, is essential for angiogenesis during mouse development. Mutations in the human gene cause hereditary hemorrhagic telangiectasia type 1 (HHT1), a disease characterized by vascular malformations that increase with age. Although haploinsufficiency is the underlying cause of the disease, HHT1 individuals show great heterogeneity in age of onset, clinical manifestations, and severity. Methods and Results-In si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 51 publications
5
107
0
8
Order By: Relevance
“…In addition, endoglin affects the efficiency of formation of the hemangioblast, a common embryonic progenitor of the hematopoietic and endothelial lineages [Perlingeiro, 2007]. Finally, supporting the relevance of endoglinexpressing circulating precursors, it was reported that endoglin has a crucial role in blood mononuclear cell-mediated vascular repair [van Laake et al, 2006]. Together, these studies support the hypothesis that endoglin expression is required for multiple cell precursors to begin tissue formation, respond to injury, and suggest that age-dependent loss of endoglin underlies an impaired response to vascular injury.…”
Section: Endoglin and Vascular Smooth Muscle Cell Developmentmentioning
confidence: 87%
“…In addition, endoglin affects the efficiency of formation of the hemangioblast, a common embryonic progenitor of the hematopoietic and endothelial lineages [Perlingeiro, 2007]. Finally, supporting the relevance of endoglinexpressing circulating precursors, it was reported that endoglin has a crucial role in blood mononuclear cell-mediated vascular repair [van Laake et al, 2006]. Together, these studies support the hypothesis that endoglin expression is required for multiple cell precursors to begin tissue formation, respond to injury, and suggest that age-dependent loss of endoglin underlies an impaired response to vascular injury.…”
Section: Endoglin and Vascular Smooth Muscle Cell Developmentmentioning
confidence: 87%
“…It is strongly expressed in endothelial cells and smooth muscle cells of blood vessels in various pathological situations, including cancer, angiogenesis and atherosclerosis [4][5][6][7][8] . It is also present on monocytes and is upregulated during monocyte-macrophage transition, playing a crucial role in monocyte-mediated vascular repair 9) . Endoglin is able to modulate the activity of different TGF-receptors, ALK-1 and ALK-5, in order to affect TGF-signaling 10) .…”
Section: Introductionmentioning
confidence: 99%
“…Anemia observed in patients with HHT1 and in Endoglin -/-mice is another indicator for a possible role of Endoglin in erythropoiesis. In the adult setting, in addition to its involvement in angiogenesis and vascular repair (Hayrabedyan et al, 2005;van Laake et al, 2006), Endoglin is expressed in long-term repopulating hematopoietic stem cells from bone marrow (Chen et al, 2002) and was reported to play a role in erythroid lineage differentiation (Moody et al, 2007). Increased levels of Endoglin expression were also found in tumors (Fonsatti et al, 2001), atherosclerotic plaques (Conley et al, 2000) and during inflammation and wound healing (Torsney et al, 2002).…”
Section: Introductionmentioning
confidence: 99%